The Relationship Between Knowledge And The Incidence Of Stunting In Bahari III, Village, Sampolawa Sub-District, South Buton District In 2024 - Hasriati, Wa Ode; Yusuf, Sulfianti A. (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
ABSTRACTSoutheast Sulawesi stunting at the age of 0-59 months reached 27% which made Southeast Sulawesi ranked 9th highest nationally. Stunting in toddlers needs special attention because it can cause inhibition of physical growth, mental development and health status in children. The results of data collection in Bahari III Village are 86 toddlers and 10 of them are stunted.A The purpose of this study was to determine the age of marriage, knowledge, education its relationship with stunting knowledge in PUS in Bahari III Village, Sampolawa District, South Buton Regency This type of research is cross sectional analytic survey research with a population of 171 and a sample of 119 with random sampling technique. The results showed that there was a significant relationship between age of marriage of 0.004 (<0.05), education of 0.03 (<0.05), and income on knowledge about stunting.. Cross-sectoral cooperation is needed to deal with the problem of stunting and to promote the dissemination of information and motivation related to stunting in all circles of society.